PENGEMBANGAN SISTEM SMART AQUAPONIK - Zulhelman Zulhelman; Haidar Afkar Ausha; Rachma Maharani Ulfa (Jurnal Poli-Teknologi, 2016)
ABSTRACTThe demand to using small space for agriculture is increasingly high on communities in Indonesia, especially in major cities. Thus, it needs a modern agricultural model which does not take some spaces and time, but also it can produce maximum yields. One of the models of modern farming in urban areas that are popular among communities is Aquaponics. The traditional Aquaponics is developed into a Smart Aquaponics. Smart Aquaponics is a system of joint fisheries and aquaculture plants in one container that runs automatically. The basic core of the system is the optimum water supply for each commodity (fisheries and aquaculture plants, red) and utilize the water recirculation system that requires intensive care for the monitoring system. To improve the system, it takes an Aquaponics embedded systems that are already developed, so it could monitor the PH levels of water, water height and food supply for fishes that already integrated to mobile application and internet network in real-time.Keywords: smart aquaponics, embedded system, real-time mobile applicationABSTRAKPermintaan kebutuhan untuk memanfaatkan lahan terbatas untuk pertanian semakin tinggi pada masyarakat di Indonesia, khususnya pada masyarakat di kota-kota besar. Sehingga diperlukan sebuah model pertanian modern yang tidak memakan tempat yang lebih banyak dan waktu yang terbuang, namun dapat menghasilkan hasil panen yang maksimal. Salah satu model pertanian modern di perkotaan (Urban Agriculture) yang sedang berkembang di kalangan masyarakat perkotaan adalah aquaponik. Aquaponik yang tradisional dikembangkan menjadi Smart Aquaponik. Smart aquaponik adalah sebuah sistem budidaya gabungan antara perikanan dan tanaman dalam satu wadah secara otomatis. Inti dasar dari sistem tersebut adalah penyediaan air yang optimum untuk masing-masing komoditas dan memanfaatkan sistem resirkulasi air, yang mana membutuhkan perawatan yang intensif untuk me-monitoring sistem tersebut. Untuk menyempurnakan sistem tersebut, dibutuhkan sebuah sistem embedded aquaponic pintar (smart aquaponic) yang sudah dikembangkan yang dapat me-monitoring kadar ph air, ketinggian air, dan pakan ikan yang terintergrasi dengan mobile application dan jaringan internet secara real-time. Sehingga, mobilitas pengguna aquaponik dapat lebih mudah dan efisien.Kata kunci: smart aquaponic, sistem embedded, real-time mobile application